Nature and relationships of Sahelanthropus tchadensis. Issue 149 (December 2020) - Macchiarelli, Roberto; Bergeret-Medina, Aude; Marchi, Damiano; Wood, Bernard
Abstract: A partial left femur (TM 266-01-063) was recovered in July 2001 at Toros-Menalla, Chad, at the same fossiliferous location as the late Miocene holotype of Sahelanthropus tchadensis (the cranium TM 266-01-060-1). It was recognized as a probable primate femur in 2004 when one of the authors was undertaking a taphonomic survey of the fossil assemblages from Toros-Menalla. We are confident the TM 266 femoral shaft belongs to a hominid. It could sample a hominid hitherto unrepresented at Toros-Menalla, but a more parsimonious working hypothesis is that it belongs to S . tchadensis . The differences between TM 266 and the late Miocene Orrorin tugenensis partial femur BAR 1002′00, from Kenya, are consistent with maintaining at least a species-level distinction between S. tchadensis and O. tugenensis. The results of our preliminary functional analysis suggest the TM 266 femoral shaft belongs to an individual that was not habitually bipedal, something that should be taken into account when considering the relationships of S . tchadensis . The circumstances of its discovery should encourage researchers to check to see whether there is more postcranial evidence of S . tchadensis among the fossils recovered from Toros-Menalla.